Miniaturized wideband coupler for 60-GHz band in 65-nm CMOS technology - Chew, Peng Siew (2019)
A compact and wideband coupler for the 60-GHz frequency band applications using 65-nm CMOS technology is presented. By meandering the coupled line, a miniaturized coupler can be obtained. The proposed coupler achieves a measured insertion loss between the input port and the through port (S 21 ) of 6.3 dB and between the input port and the coupled port (S 31 ) of 5.6 dB at 60 GHz. The measured amplitude imbalance and phase difference are 0.75 dB and 92°, respectively, at 60 GHz. Overall, the proposed coupler can achieve a measured amplitude imbalance of <;1 dB, phase imbalance of <;4°, return loss, and isolation better than 13 and 20 dB, respectively, from 50 to 67 GHz. In addition, the proposed coupler occupies a core area of only 156 μm × 157 μm (0.024 mm 2 ).